1984
DOI: 10.1002/j.1460-2075.1984.tb01784.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that positional information is used to establish the prestalk-prespore pattern in Dictyostelium discoideum aggregates

Abstract: Two contrasting mechanisms have been proposed for the establishment of the prestalk‐prespore pattern in the multicellular aggregate of the simple eukaryote Dictyostelium discoideum. One involves intermingled, non‐position‐dependent cell differentiation followed by sorting out which produces the pattern of prestalk cells in the anterior region and prespore cells posteriorly. The second mechanism involves patterning according to the position of cells within the aggregate, in which case intermingled cell types ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 23 publications
5
33
0
Order By: Relevance
“…They are also consistent with the results of Takeuchi and co-workers, who used antibodies against a carbohydrate moiety common to prespore proteins ITakeuchi 1963;Tasaka et al 1983;Takemoto et al 1985;Gomer et al 1986a). The localized developmental pattern of SP60 expression reveals the initial patterning of prespore cells and is consistent with the involvement of spatial determinants in this process and with the results of Krefft et al (1984) for the D19 gene product.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…They are also consistent with the results of Takeuchi and co-workers, who used antibodies against a carbohydrate moiety common to prespore proteins ITakeuchi 1963;Tasaka et al 1983;Takemoto et al 1985;Gomer et al 1986a). The localized developmental pattern of SP60 expression reveals the initial patterning of prespore cells and is consistent with the involvement of spatial determinants in this process and with the results of Krefft et al (1984) for the D19 gene product.…”
Section: Discussionsupporting
confidence: 84%
“…This is also consistent with earlier two-dimensional gel results examining the expression of SP60 in dissected anterior and posterior portions of migrating slugs and mature spores (Devine et al 1983;Morrissey et al 1984). A similar pattern is seen for the prespore gene DI9, which encodes a protein found in the slime sheath surrounding the migrating slug, through the use of monoclonal antibodies and lacZ fusion constructs (Krefft et al 1984;Dingermann et al 1990). Untransformed cells (see…”
Section: Spatial Expression Of Fusion Gene Productssupporting
confidence: 88%
See 1 more Smart Citation
“…Figure 1A shows the typical pattern of labelling of untreated slug cells with monoclonal antibody MUD1, which specifically labels the surface of prespore cells (9). Note that both FALS and LI90 are appreciable for these unpermeabilised cells.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from several laboratories have suggested that prestalk and prespore cells arise in a spatially random manner throughout the aggregate and that sorting results from cell-type specific alterations in adhesion (Abe et al, 1994;Nicol et al, 1999). However, it has also been proposed that pattern can be generated by position-dependent differentiation of the different cell types (Krefft et al, 1984;Wolpert, 1981). The positional information model states that the value related to a position in a coordinate system determines cell differentiation (Wolpert, 1989;Wolpert and Szathmary, 2002).…”
Section: Research Articlementioning
confidence: 99%